EFFECTS OF EXOGENOUS DIGESTIVE ENZYMES ON NILE TILAPIA FED PRACTICAL DIETS - ADEOYE, A. A; FAWOLE, F. J; YOMLA, R. (Nigerian Journal of Fisheries, 2017)
A study was carried out to evaluate the effects of exogenous digestive enzymes on all male Nile tilapia (Oreochromis niloticus) fed practical diets. The tilapia (29.52±0.3g, 40 fish per tank) was fed one of diets supplemented with phytase (75 mg kg-1 ), protease (300 mg kg-1 ), xylanase (250 mg kg-1 ) and control diet. The tilapia was fed at 3 % biomass per day in triplicate tanks per treatment for 8 weeks. The final body weight of tilapia fed xylanase supplemented diet was significantly higher (P < 0.05) than that of tilapia fed the remaining three diets (136.42±0.41, 137.09±1.5 and 135.26 g fish-1 for control, phytase and protease supplemented diets respectively). Also, the protein efficiency ratio was highest (P < 0.05) in tilapia fed xylanases supplemented diet. However, there was no significant (P > 0.05) difference observed in specific growth rate, somatic indices, survival and haematoimmunological parameters of tilapia fed the experimental diets. The histological assessment of mid-intestine sections taken from the tilapia also showed no significant difference in their perimeter ratio and number of secretory goblet cells per 100 μm. It could therefore be concluded that tilapia does not benefit markedly from a practical diet supplemented with costly exogenous digestive enzymes.